Personal Determinants of Young Adults' Willingness to Use OTC Painkillers - Izabella Maria Łukasik; Agnieszka Buczak (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: OTC painkillers are among the most commonly used pharmaceuticals. The widespread availability of painkillers is not the only predictor of willingness to use them, although it may encourage underestimation of side effects, unwarranted use and overdose. Research Aim: The aim of the study was to determine the relationship between personal resources (self-efficacy, positive future orientation and locus of pain control), and willingness to use OTC painkillers. Method: A survey was conducted among 252 young adults aged 17-26 years, including 183 (72.6%) women and 69 (27.4%) men. A tool was constructed to study the willingness to use pain medication by referring to Ajzen's Theory of Planned Behaviour. The scale has satisfactory psychometric properties. Results: Internal pain control, self-efficacy and positive future orientation promote caution in the use of OTC painkillers. People with high levels of self-efficacy and those with higher levels of positive future orientation show greater awareness of the health risks of OTC painkillers. A factor that increases willingness to take OTC painkillers is attributing the importance of random events for pain control. Respondents with a low level of internal pain control are statistically more likely, than those with a high level, to be in favour of eliminating suffering with painkillers, are more likely to use medication habitually. Conclusion: Personal resources such as locus of pain control, self-efficacy, and positive future orientation significantly modify willingness to use painkillers.